Synergy of Work Environment, CEO Characteristics, and MSME Performance: A Case Study in Indonesia’s Clothing Industry - Judijanto, Loso; Murthada, Murthada; Putra, Alfa Santoso Budiwidjojo; Astuti, Ambar Kusuma (International Journal of Business, Law, and Education, 2023)
This research investigates the synergistic impact of the work environment and CEO characteristics on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia's clothing industry. The study explores the significance of these factors in enhancing MSME performance and aims to contribute both theoretically and practically to the understanding of these dynamics. Utilizing a quantitative research approach, the study analyzes data from 276 MSMEs in the clothing industry, employing the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results indicate a positive and significant influence of the work environment and CEO characteristics on MSME performance. The research provides valuable insights for policymakers, business leaders, and industry associations to optimize work environments and select CEOs with specific attributes to improve MSME performance.